Knowledge of, and participation in, advance care planning: A cross-sectional study of acute and critical care nurses' perceptions. (October 2018) - Shepherd, Jan; Waller, Amy; Sanson-Fisher, Rob; Clark, Katherine; Ball, Jean
Abstract: Background: Nurses have a core role in facilitating discussions and enacting decisions about end-of-life issues for patients in hospitals. Nurses' own knowledge and attitudes may influence whether they engage in meaningful end-of-life conversations with patients. Aims: To determine in a sample of nurses working in acute and critical care hospital wards: 1) their knowledge of advance care planning, including the authority of substitute decision-makers and legal validity of advance directives; 2) their own participation in advance care planning decision-making practices; and 3) associations between nurses' socio-demographic characteristics; clinical expertise; and knowledge and behaviour in relation to advance care planning practices. Design: Questionnaire-based, cross-sectional study. Setting and participants: The study was conducted with 181 registered and enrolled nurses employed in acute and critical care wards of three metropolitan hospitals in Australia. Results: Nurses were least knowledgeable about items relating to the authority of medical (56%) and financial (42%) substitute decision-makers. Few nurses had prepared advance directives (10%) or appointed medical (23%) or financial (27%) decision-makers, when compared to discussing end-of-life wishes (53%) or organ donation (75%). Overall, 15% of nurses had not engaged in any advance care planning practices. Nurses who had cared for 11–30 dying patients in the last six months were more likely to have an increased knowledge score. Older nurses were more likely to participate in a greater number of advance care planning practices and an increase in shifts worked per week led to a significant decrease in nurses' participation. Conclusion: Nurses have a key role in providing advice and engaging dying patients and their families in advance care planning practices. Nurses' own knowledge and rates of participation are low. Further education and support is needed to ensure that nurses have an accurate knowledge of advance care planning practices, including how, when and with whom wishes should be discussed and can be enacted.